Study of the Impact of Climatic Changes in 1980–2021 on Railway Infrastructure in the Central and Western Russian Arctic Based on Advanced Electronic Atlas of Hydrometeorological Parameters (Version 2, 2023) - Gvishiani Alexei; Rozenberg Igor' Naumovich; Soloviev Anatoly; Krasnoperov Roman; Shevaldysheva Olga; Kostianoy Andrey Gennad'evich; Lebedev Sergey; Dubchak Irina; Sazonov Nikolay; Nikitina Isabella; Gvozdik Sofia A.; Sergeev Vladimir; et al. (Russian Journal of Earth Sciences, 2023)
Arctic zone of the Russian Federation (AZRF) is the region of intensive economic development. In this regard, it is critical to give an adequate assessment of natural factors that may have a negative impact on the growing technological infrastructure. Rapid climate change effects show a significant influence on this activity, including the railway network development. Hence, the decision-making community requires relevant information on climatic variations that can put at hazard the construction and operation of railway facilities. This paper presents the analysis of climatic changes within the region of Central and Western Russian Arctic in 1980–2021. It was performed using the new electronic Atlas of climatic variations in main hydrometeorological parameters, created for the Russian Railways in 2023. This geoinformatic product includes about 400 digital maps reflecting the variability of seven climatic parameters over more than four decades within the studied region. These parameters are air temperature, total precipitation, wind speed, soil temperature, soil moisture content, air humidity, and snow cover thickness. The analysis of climatic maps and their comparison between selected periods showed spatial and temporal heterogeneity of climatic variations in this region. This justifies the feasibility of further research using additional analytical instruments, such as Hovmöller diagrams, time series graphs, etc. The implementation of advanced geoinformatic products in the practice of the Russian Railways will facilitate sustainable development of its infrastructure in rapidly altering climatic conditions.